2012
DOI: 10.1002/anie.201108132
|View full text |Cite
|
Sign up to set email alerts
|

Dual Acquisition Magic‐Angle Spinning Solid‐State NMR‐Spectroscopy: Simultaneous Acquisition of Multidimensional Spectra of Biomacromolecules

Abstract: Fast data collection: A general method for dual data acquisition of multidimensional magic‐angle spinning solid‐state NMR experiments is presented (see picture). The method uses a simultaneous Hartmann–Hahn cross‐polarization from 1H to 13C and 15N nuclei and exploits the long‐living 15N polarization for parallel acquisition of two multidimensional experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 59 publications
4
95
0
Order By: Relevance
“…The sequence for a three-dimensional 1 H detection experiment is shown in Figure 1A. One and two-dimensional experiments with 1 H detection and simultaneous correlation to 13 C and 15 N nuclei were adapted from previous publications using simultaneous cross polarization (CP) [14, 15, 17] and concurrent cross polarization pulse schemes [27]. 1 H magnetization is transferred to 13 C and 15 N simultaneously using Hartmann-Hahn CP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence for a three-dimensional 1 H detection experiment is shown in Figure 1A. One and two-dimensional experiments with 1 H detection and simultaneous correlation to 13 C and 15 N nuclei were adapted from previous publications using simultaneous cross polarization (CP) [14, 15, 17] and concurrent cross polarization pulse schemes [27]. 1 H magnetization is transferred to 13 C and 15 N simultaneously using Hartmann-Hahn CP.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, 13 C/ 13 C homonuclear correlation under proton assisted recoupling (PAR) and 13 C/ 15 N heteronuclear correlation under proton-assisted insensitive nuclei (PAIN) can be performed using simultaneous spin-lock pulses on three channels under second-order recoupling schemes. In addition, recently, it has been shown that bidirectional cross-polarization between 13 C and 15 N nuclei can be used to transfer coherence without significant losses in signal intensities [15, 17]. This has enabled triple-resonance experiments to be executed with multiple acquisitions using a single receiver within a single experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has been redesigning the classical MAS ssNMR experiments for resonance assignment and distance determination in biological solids, boosting both sensitivity and resolution [912]. Toward this goal, we developed a new class of experiments called Polarization Optimized Experiments (POE) that utilize orphan spin operators to generate up to eight multi-dimensional NMR spectra from one pulse sequence [9, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal, we developed a new class of experiments called Polarization Optimized Experiments (POE) that utilize orphan spin operators to generate up to eight multi-dimensional NMR spectra from one pulse sequence [9, 13]. These experiments are performed using commercial ssNMR probes for bio-solids and require only one receiver.…”
Section: Introductionmentioning
confidence: 99%
“…While in liquid-state NMR there are several pulse sequences designed to detect discarded coherences via dual receivers or phase cycling schemes, 4 in ssNMR there are only a few examples that utilize orphan (i.e., neglected) spin operators to boost sensitivity. [5][6][7][8][9][10][11][12][13] In general, classical ssNMR pulse sequences eliminate orphan spin operators of magnetization either using z-filters or phase cycling schemes that suppress the spectral artifacts arising from undesired coherence transfer pathways.…”
Section: Introductionmentioning
confidence: 99%